Motivations for voluntary financial reporting by Religious Non-profit Organisations (RNPOs) in Malaysia: A conceptual paper - Rozaidy Mahadi; Noor Kaziemah Sariman; Zubaidah Mohd Ali (Universal Publishers, 2022)
The study attempts to discuss the feasible motivations that drive RNPOs in Malaysia to perform voluntary financial reporting despite having no mandatory obligations to do so. Institutional logic will be used as a theoretical insight to explain the motivations of voluntary reporting. Qualitative approach is chosen as a proposed methodology to collect primary data through semi-structured interviews with selected RNPOs representing the main four religions in Malaysia. Data triangulation will be utilised in analysing the primary findings with the related documents review. The study will employ field-level analysis which focuses on emergence field-level structure to understand the interplay of institutional logics at a lessfocused institutional field. The study attempts to provide a greater understanding of the underlying motivations for a less-regulated organisational structure to adopt comprehensive private-alike practices. The study explores the implication of highly fragmented fields in one of the less-researched areas in institutional logic (i.e., emergent field), especially in discussing how contesting multiple logics were aligned and realigned by the organisational actors in achieving legitimacy at different organisational settings.